CINEMAS, THEATRES AND MUSEUMS IN UZBEKISTAN (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
: Uzbekistan's artistic spirit dances to a rhythm woven from centuries of cultural exchange. From the echoes of Silk Road merchants traversing ancient trade routes to the indelible mark of the Soviet era, the country's artistic landscape is a vibrant tapestry of influences. Cinemas, theaters, and museums act as windows into this rich history and evolving cultural identity, showcasing a captivating blend of traditional art forms and contemporary artistic expressions.